Uterine torsion of 90 degrees: case report - Tanouti, S.; Chakri, M.; Taheri, H.; Saadi, H.; Mimouni, A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Uterine torsion is defined as a rotation of uterus more than 45 degrees along its long axis. However, a pathologic rotation of the uterus beyond 45 degrees-torsion of the entire uterus-is rarely seen in obstetrical practice, authors report a case of torsion of the uterus by 90 degrees. The patient, a 30-year-old gravida 3 para 2 at 37 weeks’ gestation with a singleton pregnancy, her prior obstetrical history included two uncomplicated term vaginal deliveries, and the current pregnancy had been uncomplicated until the date of presentation was admitted to the obstetrical unit with labour at 37 weeks 5 days ,on obstetric examination the patient was in labour with transversal presentation of the fetus so an emergency caesarean section (CS) was carried out for. At the time of CS, the diagnosis of uterine torsion of 90 degrees was made. After the delivery of the baby, uterus returned to anatomical position and the torsion corrected spontaneously. The patient recovered and was discharged home with her baby on the third postoperative day. Uterine torsion is an infrequently reported and potentially dangerous complication of pregnancy that occurs mainly in the third trimester.